Electrochemical performance of Na2MnPO4F/C cathode synthesized through a solid-state method with variation of carbon concentration between citric acid and coconut shell charcoal - Nugraha Ramadhan (Journal of Innovation Materials, Energy, and Sustainable Engineering, 2026)
Background: The increasing demand for sustainable and low-cost energy storage systems has encouraged the development of sodium-ion batteries as an alternative to lithium-ion batteries. However, the low electronic conductivity and slow Na⁺ diffusion kinetics of Na₂MnPO₄F remain major limitations for its cathode performance. Methods: In this study, Na₂MnPO₄F/C cathode materials were synthesized using a solid-state method with carbon coating derived from citric acid and coconut shell charcoal at concentrations of 0, 3, 5, and 7 wt.%. Findings: Structural characterization confirmed the successful formation of the Na₂MnPO₄F phase, where citric acid at 7 wt.% produced the highest phase purity (99.9%), while coconut shell charcoal achieved the highest purity at 3 wt.% (90.066%). SEM-EDX analysis revealed that increasing carbon concentration influenced particle morphology, elemental distribution, and surface porosity, while FTIR analysis confirmed the presence of Mn–O, PO₄, and C–C bonding within the composites. Electrochemical characterization using EIS demonstrated that carbon coating significantly improved charge-transfer behavior, with the 7 wt.% citric acid sample exhibiting the lowest resistance and the best electron transport capability. Conclusion: These findings indicate that carbon coating, particularly using citric acid, effectively enhances the structural stability and electrochemical performance of Na₂MnPO₄F cathodes, highlighting its potential for sustainable sodium-ion battery applications. Novelty/Originality oh this article: The use of carbon coating derived from citric acid and coconut shell charcoal at concentrations of 0, 3, 5, and 7 wt.% on Na₂MnPO₄F/C cathode materials successfully improved charge-transfer behavior, structural stability, and electron transport capability, particularly in the 7 wt.% citric acid sample which exhibited the lowest resistance and the best electron transport capability.